2022
DOI: 10.1177/17562872221122484
|View full text |Cite
|
Sign up to set email alerts
|

Antimuscarinics for neurogenic overactive bladder in multiple sclerosis: real-life data

Abstract: Background: Antimuscarinics (AMs) represent the mainstay of treatment for storage lower urinary tract symptoms (LUTS) but few data are available on their impact in multiple sclerosis (MS) patients. Objective: To assess effectiveness and tolerability of AMs in MS patients with neurogenic detrusor overactivity (NDO). Methods: Sixty consecutive outpatients, who started treatment with AMs at one centre, were recruited. The primary endpoint was change in Patient’s Perception of Intensity of Urgency Scale (PPIUS) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Both solifenacin 10 mg and oxybutynin immediate release 15 mg treatments resulted in an improvement of the urodynamic parameters and quality of life 16 . Another study has been conducted recently by Andretta et al, which resulted to a significant improvement in storage lower urinary tract symptoms in 73.3% of the cases, with a moderate risk of urinary retention as demonstrated by the average increase of PVR 17 . It is also stated that positive outcomes were obtained by dosage titration or combination of different AMA.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Both solifenacin 10 mg and oxybutynin immediate release 15 mg treatments resulted in an improvement of the urodynamic parameters and quality of life 16 . Another study has been conducted recently by Andretta et al, which resulted to a significant improvement in storage lower urinary tract symptoms in 73.3% of the cases, with a moderate risk of urinary retention as demonstrated by the average increase of PVR 17 . It is also stated that positive outcomes were obtained by dosage titration or combination of different AMA.…”
Section: Discussionmentioning
confidence: 96%
“…There are limited studies assessing tolerability of AMA among MS patients, yet the studies indicated low percentage of withdrawal because of intolerability. The side effects can sometimes be irrelevant with the dosage, yet in some occasions, dosage is increased to improve the efficacy and at that time side effects can occur 15–17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations